Transfusão Permuta Parcial em Crianças e Jovens com Doença Falciforme: Comparação da Experiência Manual com o Procedimento Automatizado - Escobar, C (2017)
INTRODUCTION: The benefits of manual versus automated red blood cell exchange have rarely been documented and studies in young sickle cell disease patients are scarce. We aim to describe and compare our experience in these two procedures. MATERIAL AND METHODS: Young patients (≤ 21 years old) who underwent manual- or automated-red blood cell exchange for prevention or treatment of sickle cell disease complications were included. Clinical, technical and hematological data were prospectively recorded and analyzed. RESULTS: Ninety-four red blood cell exchange sessions were performed over a period of 68 months, including 57 manual and 37 automated, 63 for chronic complications prevention, 30 for acute complications and one in the pre-operative setting. Mean decrease in sickle hemoglobin levels was higher in automated-red blood cell exchange (p < 0.001) and permitted a higher sickle hemoglobin level decrease per volume removed (p < 0.001), while hemoglobin and hematocrit remained stable. Ferritin levels on chronic patients decreased 54%. Most frequent concern was catheter outflow obstruction on manual-red blood cell exchange and access alarm on automated-red blood cell exchange. No major complication or alloimunization was recorded. DISCUSSION: Automated-red blood cell exchange decreased sickle hemoglobin levels more efficiently than manual procedure in the setting of acute and chronic complications of sickle cell disease, with minor technical concerns mainly due to vascular access. The threshold of sickle hemoglobin should be individualized for clinical and hematological goals. In our cohort of young patients, the need for an acceptable venous access was a limiting factor, but iron-overload was avoided. CONCLUSION: Automated red blood cell exchange is safe and well tolerated. It permits a higher sickle hemoglobin removal efficacy, better volume status control and iron-overload avoidance.